Transferability of health-related quality of life data of large observational studies to clinical practice: comparing retroperitoneal sarcoma patients from the PROSa study to a TARPS-WG cohort - Jakob, Jens; Hentschel, Leopold; Richter, Stephan; Kreisel, Inga; Hohenberger, Peter; Kasper, Bernd; Andreou, Dimosthenis; Pink, Daniel; Schmitt, Jochen; Schuler, Markus K.; Eichler, Martin (Oncology research and treatment, 2022)
Introduction: Health-related quality of life (HRQoL) is crucial for shared decision-making. The “Patient-Reported Outcome measures in Sarcoma” (PROSa) study evaluated HRQoL in general. We evaluated the transferability of PROSa data to clinical practice for the subgroup of retroperitoneal sarcoma (RPS). Methods: To obtain a PROSa-RPS cohort, we excluded patients with bone sarcomas and gastrointestinal stromal tumors from the complete PROSa cohort (n = 1,113), limited tumor localization to trunk and retroperitoneum, and excluded patients with metastases. We evaluated the HRQoL data of the resulting 76 patients and compared their clinical data to those of the Transatlantic Autralasian Retroperitoneal Sarcoma Working Group (TARPS-WG, n = 1,007). Results: Confidence intervals for patient sex, histological subtype (LPS vs. non-LPS), grading (G1 vs. G2/3), surgical margins (R2 vs. no R2), and perioperative chemo- and radiotherapy (yes vs. no) were overlapping in both cohorts. EORTC QLQ-C30 from RPS-PROSa patients demonstrated that two-thirds had clinically relevant restrictions in physical functioning. Two-thirds reported dyspnea, followed by fatigue and pain. Conclusion: Clinical data from RPS-PROSa patients are comparable to those of an RPS reference cohort from expert centers. We believe that HRQoL data of RPS patients extracted from PROSa are transferable to clinical practice.